Low and high repetition frequency femtosecond lasers processing of tungsten-based thin film. (22nd October 2014) - Gaković, B.; Petrović, S.; Krmpot, A.; Pantelić, D.; Jelenković, B.; Stratakis, E.; Fotakis, C.
Abstract In this work we reported low and high repetition frequency femtosecond laser-induced modifications of tungsten-based thin film. The tungsten-titanium (WTi) thin film, thickness of 190 nm, was deposited by sputtering on single crystal Si (100) wafer. Irradiations were performed in air by linearly polarized and focused femtosecond laser beams with following parameters: (1) pulse duration 160 fs, wavelength 800 nm, laser repetition frequency (LRF) 75 MHz — high LRF, and (2) duration 40 fs, wavelength 800 nm, LRF of 1 kHz — low LRF. The results of femtosecond lasers processing of the WTi thin film revealed laser induced periodical surface structures (LIPSS) in the case of low LRF regime. LIPSSs were formed with different periodicity and different orientation to the laser polarization at the surface: micro-scale LIPSSs with orientation perpendicular to the laser polarization and nano-scale LIPSSs parallel and perpendicular to the laser polarization. After processing of the WTi/Si system in high LRF regime ablation and nano-particles formation were registered.